Banks Stress Tests - Dušková, Kamila; Blahová, Naďa, 1958-; Boháčik, Ján; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
The bachelor’s thesis deals with the topic of stress testing in the banking sector. It consists of three main parts. The first part defines stress tests as a tool that assesses the readiness of banking system for improbable but possible events. It describes the approaches, the process and the classification of testing and risks typical for the banking sector in detail. The second chapter focuses on CNB (Czech National Bank) stress tests published in 2018. This chapter includes hypothetical scenarios of the development of economy with a subsequent analysis of their impact on the bank balance sheet and on the whole banking system. The last chapter is dedicated to European stress tests with an emphasis on tests published in 2018 by EBA. The chapter includes the basic description of the performed tests, the summary of their results and the evaluation of the resilience of the European banking system.
Vedoucí práce: Naděžda Blahová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses